2022
DOI: 10.1681/asn.2021030383
|View full text |Cite
|
Sign up to set email alerts
|

Bone Marrow–Derived RIPK3 Mediates Kidney Inflammation in Acute Kidney Injury

Abstract: BackgroundReceptor-interacting protein kinase 3 (RIPK3), a component of necroptosis pathways, may have an independent role in inflammation. It has been unclear which RIPK3-expressing cells are responsible for the anti-inflammatory effect of overall Ripk3 deficiency and whether Ripk3 deficiency protects against kidney inflammation occurring in the absence of tubular cell death.MethodsWe used chimeric mice with bone marrow from wild-type and Ripk3-knockout mice to explore RIPK3′s contribution to kidney inflammat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 43 publications
0
17
0
Order By: Relevance
“…Targeting of TWEAK or necroptosis shortened the duration of AKI, and led to improved kidney function and histology 96 h after exposure to folic acid in mice. However, in one study, specific targeting of bone marrow-derived RIPK3 induced an early decrease in kidney inflammation independent of effects on tubule cell death and did not improve kidney function 48 h after administration of folic acid 65 , suggesting that RIPK3 might have a dual role in FA-AKI by promoting both early inflammation through its function in innate immune cells and later tubule cell necroptosis in response to inflammatory cytokines through its function in tubular cells. FA-AKI has also been used as a model to explore the effect of ferroptosis on the lipidome 103 , 117 , 175 .…”
Section: Regulated Necrosis In Kidney Diseasementioning
confidence: 96%
See 1 more Smart Citation
“…Targeting of TWEAK or necroptosis shortened the duration of AKI, and led to improved kidney function and histology 96 h after exposure to folic acid in mice. However, in one study, specific targeting of bone marrow-derived RIPK3 induced an early decrease in kidney inflammation independent of effects on tubule cell death and did not improve kidney function 48 h after administration of folic acid 65 , suggesting that RIPK3 might have a dual role in FA-AKI by promoting both early inflammation through its function in innate immune cells and later tubule cell necroptosis in response to inflammatory cytokines through its function in tubular cells. FA-AKI has also been used as a model to explore the effect of ferroptosis on the lipidome 103 , 117 , 175 .…”
Section: Regulated Necrosis In Kidney Diseasementioning
confidence: 96%
“…However, additional canonical and non-canonical pathways for RIPK3 activation exist that do not require RIPK1 63 , 64 (Fig. 3c ); moreover, RIPK3 can promote inflammatory responses independent of necroptosis 65 , 66 . In kidney cells, inhibition of caspases prevents apoptosis, but may lead to RIPK1-mediated necroptosis, as observed in a model of cytokine-induced tubule cell death 18 , 67 .…”
Section: Regulated Necrosismentioning
confidence: 99%
“…Numerous studies indicate that macrophages are a major contributor to the inflammatory response of AKI ( Huen and Cantley, 2017 ; Martin-Sanchez et al, 2022 ). Macrophage-induced inflammatory and fibrotic responses are also key drivers of renal fibrosis, which will enhance the progression of CKD ( Chen et al, 2022 ; Zhou et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…RIPK3-caspase is crucial in the procession of macrophage differentiation ( 79 ), while how necroptosis mediated NLRP3 inflammasome activation, and mechanisms underly AKI to CKD progression remain unclear. As in tubular cells, TWEAK (TNF-like weak inducer of apoptosis) increased RIPK3 expression in macrophages however there is nothing known about RIPK1 ( 80 ). Macrophages conditional knockout mice also are involved in decreasing expression of MCP-1, IL-6, IL-1β like in renal tubular cells.…”
Section: The Pathways Of Macrophage Pro-inflammationmentioning
confidence: 99%
“…Macrophages conditional knockout mice also are involved in decreasing expression of MCP-1, IL-6, IL-1β like in renal tubular cells. Moreover, RIPK3 in macrophages promotes NF- κ B–dependent release of proinflammatory cytokines and activates the NF- κ B signaling pathway, in turn, promoting macrophage-tubular crosstalk that recruits inflammatory responses from tubular cells ( 80 ). Evidence has shown that necroptosis plays a crucial part in the early progression of multiple types of AKI ( 81 , 82 ).…”
Section: The Pathways Of Macrophage Pro-inflammationmentioning
confidence: 99%